3D-printed polycaprolactone combined with cartilage acellular matrix tissue engineered cartilage scaffold manufactured by low-temperature deposition manufacturing - Song, Zhen; Zhang, Xulong; Xu, Yihao; Ji, Jingyuan; Sun, Wei; Fan, Fei; You, Jianjun; Pang, Yuan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTissue-engineered cartilage provides an alternative for tissue repair and reconstruction. Composite scaffolds incorporating acellular cartilage matrix (ACM) and synthetic polymers have shown particular promise for cartilage tissue engineering applications. However, the present composite scaffold has not been considered as a clinically available application due to insufficient mechanical property or inflammatory response.MethodsThis study presents the composite scaffold composed of ACM and polycaprolactone (PCL) prepared by the low-temperature deposition manufacturing (LDM).ResultsThe PCL/ACM scaffold exhibited a Young’s modulus of 462 ± 119 kPa and a compressive yield stress of 592 ± 87 kPa. After 2 weeks in vitro, cell viability presents 92.36% ± 13.41% in PCL/ACM scaffold. Quantification through type II collagen immunofluorescence intensity measurements, exhibited a 1.85-fold increase (p < 0.001) in the PCL/ACM group relative to PCL controls.Discussion:Through LDM, the ACM was uniformly bond to PCL, resulting in satisfactory mechanical properties of the scaffold. Additionally, the scaffold had a multi-scale structure including microscale pores and nanoscale pores, which increased the porosity of the scaffold. Finally, cartilage-specific extracellular matrix deposition were successfully regenerated in vivo.